Isolation, selection and characterization of lactic acid bacteria in soybean silage - Tobía, Carlos (2003)
Whole soybean plants (Glicyne max. L. Merr) harvested at the R6 state of development (full seed stage) were chopped in 2 cm pieces and stored in 1 kg microsilos, with and without previous partial dehydration (PD). Molasses at concentrations of 0, 4, and 8% were added to facilitate fermentation. A lineal decrease in pH (P≤ 0,0001) in response to an increased in molasses concentration was found. On the other hand, dry matter (DM) concentration also increased concomitantly with the concentration of molasses in the microsilos and the PD treatment (10%). No PD x molasses concentration interaction was found. Bacterial isolations were performed in microsilos with 4 and 8% molasses and without PD, because these experimental units showed the best sensorial characteristics, lower pH and lower bacterial morphotype diversity. Bacterial isolates were obtained from Rogosa agar; those corresponding to Gram positive bacilli, and catalase negative, were inoculated in Api 50 CHL® galeries for their identification as lactic acid bacteria (BAL). The isolated colonies were Lactobacillus brevis 3.